Analisis Pengaruh Nilai Pelanggan Dan Citra Merek Terhadap Kepuasan Pelanggan Pada Rumah Makan Bebek Sawah - Rezki Pertiwi Rahmadhani; Lidya Martha; Patria Nagara (JURNAL PUNDI, 2021)
Fast traslate Icon translate     Fast traslate Icon translate     Fast traslate Icon translate The purpose of this study was conducted to examine the effect of customer value and brand image on customer satisfaction at a rice field duck restaurant in the city Padang. This research method is a quantitative method, with 100 respondents as a sample to collect data through a questionnaire. The Likert scale is used with multiple regression analysis. The results showed that customer value has a positive and significant effect on customer satisfaction and image has a positive and significant effect on customer satisfaction at the rice field duck restaurant.